2008
DOI: 10.17741/bgsf/80.2.001
|View full text |Cite
|
Sign up to set email alerts
|

U-Th-Pb zircon geochronology on igneous rocks in the Toija and Salittu Formations, Orijärvi area, southwestern Finland: Constraints on the age of volcanism and metamorphism

Abstract: Zircons from a felsic volcanic rock in the Toija Formation and a synvolcanic gabbro intrusion in the Salittu Formation within the Orijärvi area were dated by U-Th-Pb SIMS in order to provide depositional constraints on these formations. Zircon crystals from the felsic rock preserve a two-stage crystallisation history with zoned core domains and homogeneous rim domains. Inner domains yield a 1878 ± 4 Ma concordia age, interpreted to determine the crystallisation of this rock. Rims yield a 1815 ± 3 Ma concordia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…1a). The preorogenic magmatism, defined as "island arc magmatism preceding onset of accretion or collision" (Nironen, 2005), comprises the 1.90-1.88 Ga volcanic rocks and their coeval plutonic magma chambers of the Häme belt and Uusimaa belts formed in volcanic arc settings (Väisänen et al 2002;Ehlers et al, 2004;Kähkönen, 2005;Väisänen and Kirkland, 2008;Saalmann et al, 2009).…”
Section: Geological Settingmentioning
confidence: 99%
“…1a). The preorogenic magmatism, defined as "island arc magmatism preceding onset of accretion or collision" (Nironen, 2005), comprises the 1.90-1.88 Ga volcanic rocks and their coeval plutonic magma chambers of the Häme belt and Uusimaa belts formed in volcanic arc settings (Väisänen et al 2002;Ehlers et al, 2004;Kähkönen, 2005;Väisänen and Kirkland, 2008;Saalmann et al, 2009).…”
Section: Geological Settingmentioning
confidence: 99%
“…However, at least locally, their intrusion took place during the last pulses of high heat flow (Vaasjoki and Sakko 1988;Väisänen et al 2000;Mouri et al 2005;Andersson et al 2006b;Baltybaev et al 2006;Väisänen and Kirkland 2008). Table 1.…”
Section: Regional Geologymentioning
confidence: 99%
“…Moreover, obtained 1878.2 ± 3.4 Ma age from a dacite from the upper part of the Kisko formation. Subsequently Väisänen and Kirkland (2008) attained 1878 ± 4 Ma concordia age from core domains of zircons from a felsic metavolcanic rock of the Toija Formation, and interpreted it to represent the crystallization of the rock. They attempted to date the SFm and although they did not get a direct age they concluded that the formation was deposited between 1878 and 1875 Ma.…”
Section: Stratigraphy and Age Correlationmentioning
confidence: 99%